Comparative transcriptomics analysis of Streptococcus mutans with disruption of LuxS/AI-2 quorum sensing and recovery of methyl cycle. (July 2021) - Yuan, Keyong; Hou, Lili; Jin, Qiaoqiao; Niu, Chenguang; Mao, Mengying; Wang, Ruirui; Huang, Zhengwei
Highlights: RNA-seq was analyzed in Streptococcus mutans with disruption of LuxS/AI-2 quorum sensing and recovery of methyl cycle . 84 genes were detected, which only affected by the LuxS/AI-2 QS system other than methyl cycle. The LuxS/AI-2 QS system mainly affects ABC transporters and carbohydrate transport, transformation and metabolism. Abstract: Objective: The LuxS/AI-2 quorum sensing (QS) system has critical roles in Streptococcus mutans cariogenicity. Whereas the molecular and cellular mechanisms of the LuxS/AI-2 QS system are not thoroughly understood. Given that LuxS has roles in QS and methyl cycle, its mutation can cause QS deficiency and methyl cycle disruption. The aim of this study was to investigate effects of the LuxS/AI-2 QS system on gene expression in Streptococcus mutans when methyl cycle was recovered with exogenous sahH gene. Methods: Our previous study introduced the exogenous sahH gene from Pseudomonas aeruginosa into an S. mutans luxS-null strain to restore the disrupted methyl cycle, and this produced the solely the LuxS/AI-2 QS system deficient strain. Here, we analyzed the transcriptomics of this strain to get insights into the molecular mechanisms of the LuxS/AI-2 QS system applying RNA-seq. Results: With recovery of methyl cycle, 84 genes didn't change in expression trends in S. mutans luxS-null strain. These genes mainly encode the ABC transporters, sugar transporter EII and enzymes of carbohydrate metabolism, and are rich in the Phosphotransferase system, Fructose and mannose metabolism, Amino sugar and nucleotide sugar metabolism, Galactose metabolism, Glycolysis/Gluconeogenesis, RNA degradation, Lysine biosynthesis, and Glycine, serine and threonine metabolism. Conclusions: The LuxS/AI-2 QS system may mainly affect ABC transporters and carbohydrate transport, transformation and metabolism via EII subunits and enzymes to influence virulence-associated traits without effects of methyl cycle in Streptococcus mutans .